NEUROTECHNOLOGIES AS INNOVATIVE TOOLS IN PEDAGOGY (Scientific journal of the Fergana State University, 2025)
This article analyzes the issues of developing students' speech through the use of neurotechnologies in the educational process. The article examines the definitions of neurotechnologies, the mechanisms of their influence on speech activity, and their use in the educational process. It also highlights the prospects for developing speech through neurotechnologies based on neurostimulation methods, neuropedagogical approaches, and the results of practical experiments. The results of this study show that neurotechnologies are an effective tool for improving students' speech skills and provide recommendations for the future use of these technologies in the educational system.